Landreform dan konflik atas tanah di Perkebunan Glenmore 1947-1970 - Faizin, Ahmad Nor (Universitas Negeri Malang, 2024)
Abstract This article is set against the background of the agrarian conflict that occurred in Glenmore Plantation from 1947-1970. The purpose of this study is to narrate chronologically the action of land claims to the implementation of land reform as a conflict resolution that occurred in Glenmore Plantation. Researchers use historical methods consisting of topic selection, heuristics, verification, interpretation, and historiography in an attempt to reconstruct the event. The sources obtained are from archives, newspapers and interviews. The results of this study explain where in the early days of independence the Dutch Government who felt that they still had rights to their plantation companies, regained control and reorganized plantation land. On the other hand, the community also has an assumption, where they also have the right to manage plantation land as a result of independence. As a result, claims to plantation land were inevitable from the early days of independence until the passing of the 1960 Law. Landreform in 1970 ended land claims at Glenmore Plantation. Abstrak Tulisan ini dilatarbelakangi dari konflik agraria yang terjadi di Perkebunan Glenmore dari tahun 1947-1970. Tujuan dari penelitian ini adalah menarasikan secara kronologis aksi klaim tanah hingga pelaksanaan landreform sebagai resolusi konflik yang terjadi di Perkebunan Glenmore. Peneliti menggunakan metode sejarah yang terdiri dari pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi dalam usaha merekonstruksi kembali peristiwa tersebut. Adapun sumber yang diperoleh adalah dari arsip, koran dan wawancara. Hasil dari penelitian ini memaparkan dimana pada masa awal kemerdekaan Pemerintah Belanda yang merasa masih memiliki hak atas perusahaan perkebunannya, kembali menguasai dan mengatur kembali tanah perkebunan. Di sisi lain masyarakat juga memiliki anggapan, dimana mereka juga berhak untuk mengelola tanah perkebunan sebagai hasil dari kemerdekaan. Akibatnya aksi klaim atas tanah perkebunan mulai terjadi sejak masa awal kemerdekaan hingga disahkannya UUPA 1960. Landreform yang terjadi pada tahun 1970 di Perkebunan Glenmore mengakhiri aksi klaim tanah.